Study on molecular interactions of l-leucine in aqueous ionic liquid (1-butyl-3-methylimidazolium tetrafluoroborate) [C4mim][BF4] solution using density, speed of sound and viscosity measurements at various temperatures. (April 2022) - Sharma, Samriti; Sharma, Shubham; Singh, Jeetinder; Singh, Manjeet; Sharma, Amit K.; Sharma, Meena
Graphical abstract: Highlights: Volumetric, acoustic and viscometric properties of L-leucine in aqueous ionic liquid solutions. Determination of hydration number. Discussion on solute–solvent interactions. Dominance of ion-hydrophilic interactions over ion-hydrophobic, hydrophobic-hydrophobic interactions. Abstract: The effect of ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate ([C4 mim][BF4 ]) (IL) on the thermophysical performance of amino acid (aa) has been examined by using viscometric, volumetric and acoustic approach. In such approach viscosity, density and speed of sound has been quantified experimentally for L-leucine in aqueous IL (0.0207, 0.0403, 0.0611) mol kg −1 solution at various temperatures (293.15–318.15) K to appraise the different parameters i.e. apparent molar properties ( V Φ, K Φ, s ), limiting apparent molar properties ( V o Φ, K o Φ, s ), limiting apparent molar transfer properties ( V o Φ, t r, K o Φ, s, t r, B tr ), viscosity coefficients A and B and hydration number ( n H ). The resulting data of evaluated parameters are resolved on the basis of co-sphere overlap model, which explain the existence of different intermolecular interactions in the system and positive transfer values signify the dominance of ionic-hydrophilic interactions. Moreover the structure making/breaking character of solute is deciphered by the temperature derivative of viscosity B -coefficients ( dB/dT ) and Hepler's constant.